1996
DOI: 10.1097/00007632-199605010-00011
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Lumbar Discectomy for the Treatment of Herniated Intervertebral Disc

Abstract: For carefully selected patients with herniated discs, surgical discectomy is a cost-effective treatment. Discectomy's favorable cost-effectiveness results from its substantial effect on quality of life and moderate costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 24 publications
2
87
1
1
Order By: Relevance
“…Whilst five full economic evaluations were identified in the systematic review [20,21,22,23,24], the majority of evaluations were undertaken in conjunction with clinical trials with a lack of published decisions models. A full narrative review of the economic evidence has been published elsewhere [11].…”
Section: Resultsmentioning
confidence: 99%
“…Whilst five full economic evaluations were identified in the systematic review [20,21,22,23,24], the majority of evaluations were undertaken in conjunction with clinical trials with a lack of published decisions models. A full narrative review of the economic evidence has been published elsewhere [11].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Parker et al 17 found that the mean cost per patient for primary discectomy surgery was similar to that for revision discectomy, $42,554. In a randomized study, Malter et al 13 analyzed insurance data from 372 patients who had undergone discectomy and found that the mean cost for these patients was $13,390.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a higher utility was assigned to CDR than ACDF, reflecting a better overall neurological status, overall success, and improved range of motion in the CDR group. 20,35 Sensitivity analysis was conducted to evaluate the effect of altering the assumed utilities on the ICER of CDR.…”
Section: Utility Of Cdrmentioning
confidence: 99%
“…A review of the literature demonstrated a hardware failure rate of 0%-2% at 1 year after hardware placement. [1][2][3][4][5][6][7][13][14][15][18][19][20][21][22][24][25][26][27][28]30,31,35,36,40 Following hardware failure, a patient could undergo either a revision arthroplasty or a revision ACDF.…”
mentioning
confidence: 99%
See 1 more Smart Citation